The effect of macroeconomic variables on stock return during both non-covid and covid periods in the Chinese market - Wan, Yuxiao (2022)
This paper investigates the relationship between five macroeconomic factors and stock return in the Chinese market and explores if this plausible relationship could be varied during the covid-19 period and the non-covid period. The five macroeconomic factors researched in this paper are exchange rate, inflation, real GDP, interest rate and real money supply respectively, the stock returns refer to the returns of components stocks within three indices (SSE 50, SZSE 100, SCI 300). These data are collected from relevant academic databases for the years between 2012 to 2022 (10 years).